Enhancing Mathematical Literacy: Evaluating the Effectiveness of the ELPSA Framework in Mathematics Classrooms - Firmansyah B; Gradini, Ega; Husna, Nadiatul (Jurnal Riset Pendidikan Matematika, 2025)
This study aimed to investigate the effectiveness of the ELPSA Framework in enhancing the mathematical literacy skills of seventh-graders at SMP IT Cendekia Takengon. The research employed a quantitative approach using an experimental design. Data were collected through tests and analyzed using an independent sample t-test. The findings revealed a significant improvement in mathematical literacy skills among students in the experimental group compared to those in the control group. This improvement was evident in the N-Gain test results, indicating that 35% of the students in the experimental group achieved a high level of mathematical literacy, while 65% attained a moderate level, with an average Gain of 0.68, categorized as moderate. Moreover, the post-intervention assessment of mathematical literacy skills in the experimental group revealed that prior to ELPSA implementation, student's mathematical literacy indicated a concentration at First Level proficiency, with a smaller portion reaching Second Level. Following the introduction of the ELPSA framework, a positive shift was observed. The number of students at First Level decreased to only six, 16 students achieved Second Level, four demonstrated Third Level proficiency, six reached fourth Level, and two students achieved Fifth Level proficiency. However, none of students able to reach the Sixth level. The hypothesis test results indicated that the null hypothesis (H0) was rejected, confirming a significant difference in the improvement of mathematical literacy skills between students taught using the ELPSA Framework and those instructed using conventional teaching approaches employed by the school's teachers.